PENGARUH RATIONAL EMOTIVE BEHAVIORAL THERAPY (REBT) DALAM MENURUNKAN KECEMASAN MENGHADAPI MASA DEPAN PADA PENYALAHGUNA NAPZA DI PANTI REHABILITASI - Siburian, Evi; Karyono, Karyono; Kaloeti, Dian Sakti (Jurnal Psikologi, 2010)
Abuse of Narcotic Drugs, Psychotropic and Addictive Substance (NAPZA) can be caused by anxiety which is not normally owned by individuals. One type of anxiety is the future anxiety. Methods of handling future anxiety in this research are Rational emotive behavioral therapy (REBT). REBT is given by provide material about future anxiety, understand and change the irrational beliefs. The current study aims to determine the effect of REBT in reducing future anxiety of drug abuse in rehab. Research subject are drugs abuser who is undergoing drug rehabilitation program in Nursing Home Pamardi Putra Mandiri and has future anxiety score in the high category (minimum score 89). The design of the study is the single case of ABA design. The gathering of data was performed by using Facing the Future Anxiety Scale, interviews, and home tasks. The results of hypothesis testing that were done by visual analysis graphs of future anxiety and qualitative analysis showed that REBT programs had the effect to reduce future anxiety. The pattern of change varied between one subject with another subject. The results of follow-up showed that the results, which were obtained by the subject were affected by the commitment and consistency in applying the materials provided on the subject.Keywords : future anxiety, drugs abuse, anxiety